Ghosts of the past: The competing agendas of forensic work in identifying the missing across Bosnia and Herzegovina - Admir Jugo; Senem Škulj (Human Remains and Violence, 2015)
International interventions in Bosnia and Herzegovina, that ultimately brought the war to a standstill, emphasised recovering and identifying the missing as chief among the goals of post-war repair and reconstruction, aiming to unite a heavily divided country. Still, local actors keep,showing that unity is far from achieved and it is not a goal for all those involved. This paper examines the various actors that have taken up the task of locating and identifying the missing in order to examine their incentives as well as any competing agendas for participating in the process. These efforts cannot be understood without examining their impact both at the time and now, and we look at the biopolitics of the process and utilisation of the dead within. Due to the vastness and complexity of this process, instead of a conclusion, additional questions will be opened required for the process to keep moving forward.